OECD economic outlook. May 2013 (Paris, 2013)
"The OECD Economic Outlook is the OECD’s twice-yearly analysis of the major economic trends and prospects for the next two years. The Outlook puts forward a consistent set of projections for output, employment, prices, fiscal and current account balances.